The causal structure of the excellence model for work units. (4th July 2021) - Joshaghany, Morteza; Saghaei, Abbas; Setak, Mostafa
Abstract : The aim of this paper is to examine the relationship between the critical factors of quality management and customer outcomes in the subject of work units in organisations. The ways in which critical total quality management factors can improve the performance of a management system in work units within organisations is assessed. For this purpose, a conceptual model with specific hypotheses is suggested to test the data obtained from 86 respondents. Using structural equation models and partial least squares techniques (PLS) software, these hypotheses were tested. The findings of this research suggest that the proposed model, can be used as a reference framework for the implementation, assessment and improvement of quality in the field of work units. In this paper, we want to improve the gap in empirical research in the management of work units, and aids unit leaders to discover the variables that improve the results from client and stakeholder satisfaction.